Public Attention to Risks, Hazards, and Disasters: A Retrospective Review and Proposed Conceptual Model. Issue 3 (8th March 2019) - Silver, Amber
Abstract : Although public attention has been identified as an influential variable in the decision‐making process by individuals before, during, and after a disaster, it has received comparatively little consideration within the risk and hazards literatures. This is surprising, as attention is noted for bridging the gap between information and action, and is therefore highly relevant to studies on human behavior during crises. This paper draws on theoretical and empirical insights from research across numerous disciplines in order to flesh out the concept of public attention within the context of risks, hazards, and disasters. Theoretical insights from the literature on the issue attention cycle, agenda‐setting theory, the theory of structuration, and sense‐making theory were used to develop a conceptual model of public attention that is presented here. This model highlights the role of public attention from the moment of initial exposure, through to the iterative process of interpretation, which is intrinsically linked to action. The relationships in the conceptual model are then illustrated using two empirical research projects as examples. This paper concludes by suggesting opportunities for future research that may further improve scholarly understanding of public attention within the context of environmental hazards and other threats. Abstract : 摘要: 尽 管公众关注被认为是个体在灾害发生前、中、后期间决策过程中的重要因素，但研究风险和灾害的文献却对其予以的关注相对较少。这一点是出乎意料的，因为公众 关注能在信息和行动之间搭建桥梁，因此与危机期间人类行为的研究极为相关。本文利用不同学科研究中提取的理论和实证观点，将风险、危害和灾害背景下公众关 注这一概念进行了具体化。有 关议题关注循环、议程设置理论、结构化理论和意义建构理论的相关理论观点被用于提炼出本文呈现的公众关注概念模型。此模型强调了从最初（灾害）事件的暴露 直到事件阐述的迭代过程中公共关注的作用，后者与行动存在根本联系。概念模型中提及的各项关系随后通过两个实证研究计划进行了诠释。本文结论为今后研究提 供了机会，以便提高环境危害和其他威胁背景下对公众关注的学术理解。 Abstract : Resumen: Aunque la atención pública haya sido identificada como una variable en el proceso de toma de decisiones por parte de ciertos individuos antes, durante y después de un desastre, ha recibido comparativamente poca consideración en las literaturas de riesgo y peligro. Esto es sorprendente, ya que se entiende que la atención cierra la brecha entre la información y la acción, y por lo tanto es muy relevante para los estudios sobre el comportamiento humano durante las crisis. Este documento se basa en información teórica y empírica de investigaciones en numerosas disciplinas para elaborar el concepto de la atención pública dentro del contexto de los riesgos, peligros y desastres. Los conocimientos teóricos de la literatura sobre el ciclo de atención a problemas, la teoría del establecimiento de las agendas, la teoría de la estructuración y la teoría de la creación de sentido se utilizaron para desarrollar un modelo conceptual de atención pública que se presenta aquí. Este modelo destaca el papel de la atención pública desde el momento de la exposición inicial hasta el proceso iterativo de interpretación, que está intrínsecamente vinculado a la acción. Después se ilustran las relaciones en el modelo conceptual al utilizar dos proyectos de investigación empírica como ejemplos. Este documento concluye al proponer oportunidades para una investigación futura que podría mejorar en entendimiento académico de la atención pública dentro del contexto de los peligros ambientales y de otras amenazas.